Improving Student’s Vocabulary Mastery by Using Three Word Games at Grade VIII SMP Islam Kader Bangsa Bekasi - Nur Syifa, Putri Salsa Bila; Siahaan, Leroy Holman; Subadar, Subadar (Innovative: Journal Of Social Science Research, 2024)
The objectives of this research is to study 1) The instructional process of word games in teaching English vocabulary in SMP Islam kader Bangsa 2) The result of the implementation of word games in improving SMP Islam Kader Bangsa student’s vocabulary. This study used classroom action research in SMP Islam Kader Bangsa's VIII class in Bekasi in 2024. The model employed in this investigation was Kurt Lewin. This inquiry was divided into two cycles: planning, activity, observation, and reflection. For data collecting, the author employed both qualitative and quantitative approaches. Qualitative data was gathered by means of observations and interviews. Pre- and post-test techniques were used to gather quantitative data. The results of the study demonstrate a notable improvement in the vocabulary instruction of English through word games. While students' average score on the post-test was 89.12, their average score on the pre-test was only 64.41. With a score of 0.29 on the Sample Paired Test, all students passed the KKM.